The Effect of Light Type and Distance on Indoor Photovoltaic System - Pratiwi, Dessy Ade; Soumi, Andi Ibrahim; Kurniawan, Wafiq (Politeknik Sukabumi, 2023)
Alternative energy sources and energy storage play an important role in maintaining and providing energy. The application of indoor photovoltaic is one alternative in energy management using artificial light sources. However, one of the main obstacles faced in the operation of photovoltaic panels is the significant problem of low electrical efficiency in photovoltaic cells. The purpose of this research is to find out the performance of indoor photovoltaic with variations of LED and CFL lamps with a capacity of 5W and 10W, as well as the variation of the given distance which is 25 cm and 30 cm. The research method used is to test the temperature sensor using the MAX 6675 sensor and the voltage and current sensor using the MAX471 sensor. The light intensity produced by the lamp is read by the sensor. The electricity produced by photovoltaic is stored in the battery. The results read by the sensors are displayed on the serial monitor. The results of the research show that increasing the distance between the lamp and the light field results in a decrease in light intensity. This can be seen in the CFL lamp with a longer distance between the light source and the solar cell module which results in the light intensity of the 5W 30 cm CFL lamp being low. The decrease in the efficiency of photovoltaic systems in the room has an effect on the temperature that the increase in photovoltaic temperature causes a decrease in the efficiency of the current and voltage of the electricity output.